Approach to the Assessment and Management of Adult Patients With Atopic Dermatitis: A Consensus Document. Section II: Tools for Assessing the Severity of Atopic Dermatitis. Issue 1 (November 2018) - Gooderham, Melinda J.; Bissonnette, Robert; Grewal, Parbeer; Lansang, Perla; Papp, Kim A.; Hong, Chih-ho
Clinicians rely on clinical measures to define the severity of atopic dermatitis and assess outcomes of therapy. These measures can be objective (ie, physician assessments of disease severity) or subjective (ie, patient-reported symptoms and quality of life outcomes). In this review, the most commonly used tools for assessing atopic dermatitis severity in adult patients are presented and compared. These include Eczema Area and Severity Index (EASI); SCORing Atopic Dermatitis (SCORAD); Physician Global Assessment (PGA); body surface area (BSA); Atopic Dermatitis Severity Index (ADSI); Six Area, Six Sign Atopic Dermatitis (SASSAD); Patient Oriented Eczema Measure (POEM); Dermatology Life Quality Index (DLQI); and pruritus Numerical Rating Scale (NRS). Available severity strata for the tools are summarized, although the use of severity strata in clinical practice is not recommended. Since both objective and subjective assessments of disease severity are important to assess, consideration of clinical characteristics such as disease recurrence or persistence, as well as location of the affected areas, should be considered in the overall judgement of disease severity and consideration of therapy choice.